Critical Thinking through Interdisciplinary Texts - Regmi, Lok Raj (Tribhuvan University Journal, 2016)
Critical thinking, the art of reasoning, is a high level academic skill. It can be taught using several other resources, one of them is the use of interdisciplinary texts. This writing aims at exploring how interdisciplinary texts can be supportive to enhance students' critical thinking skill and also comprises some recommendations for a successful delivery of these texts to enhance the target skill. It concludes that the use of interdisciplinary texts is a means to teach critical thinking skill but not an end. The judicious use of them to develop students' critical thinking skill is relevant.